Elucidation of phenolic antioxidants in barley seedlings (Hordeum vulgare L.) by UPLC-PDA-ESI/MS and screening for their contents at different harvest times. (October 2016) - Lee, Jin Hwan; Park, Mi Jin; Ryu, Hyung Won; Yuk, Heung Joo; Choi, Sik-Won; Lee, Kwang-Sik; Kim, Sun-Lim; Seo, Woo Duck
Highlights: Ten phenolics in barley seedlings were identified by UPLC-PDA-ESI/MS and NMR. Lutonarin and saponarin showed remarkable differences in cultivars and harvest times. Isoorientin and orientin exhibited high scavenging effects on DPPH and ABTS radicals. The highest average phenolic was found with 2671.8 mg/100 g 23 days after sowing. Phenolic contents may be a key factor in antioxidant activities of barley seedlings. Abstract: The changes in phenolic and antioxidant capacities of seedlings of various barley cultivars through four different harvest times were investigated. Ten phenolics were characterised as hydroxycinnamic acid, orientin, isoorientin, and isovitexin derivatives using UPLC-PDA-ESI/MS and NMR. In particular, lutonarin (2 ) and saponarin (3 ) were the predominant constituents (71–75%) with significant differences in cultivars and harvest times. The highest average total phenolic content was found as 2671.8 mg/100 g on 23 days after the sowing, whereas the lowest was 1400.8 mg/100 g on 56 days. The radical scavenging abilities also exhibited considerable differences in 80% of methanol extracts (40 µg/mL), depending upon the phenolic contents. Interestingly, isoorientin (5 ) and orientin (6 ) possessed potent antioxidant effects with IC50 values of 20.7 ± 1.1 and 27.5 ± 7.3 µM (DPPH) and 5.7 ± 0.3 and 8.2 ± 0.3 µM (ABTS), respectively. These results may be contributed to enhancing the value of barley as a functional food ingredient and dietary supplement.